تقييم أسئلة اختبار أعمال السنة في مادة اللغة العربية لدى طلاب الصف الثاني الثانوي بمعهد الإمام مسلم (دراسة تحليلية من جهة سهولة البند والتمييز) - Kurniawan, Rendi; Effendi, Zulham; Hasibuan, Muhammad Syarif Muda (CV Global Research Publication, 2023)
School is a formal educational institution that provides various opportunities for students to carry out educational activities. With this educational opportunity it is hoped that the growth and development of students can achieve the expected goals. The success or failure of education in achieving its goals after evaluating the graduates produced by the school. If the graduates are in accordance with what has been set in the educational goals, then the educational effort can be said to be successful, and if on the contrary it is considered a failure in this case, it can be understood how important the assessment of learning is in education. Examination or assessment is an important component in education, especially learning assessment, and is important because assessment activities are carried out at least with the aim of knowing (1) the success of learning that has been implemented, (2) student abilities. and understanding of the material being studied, and (3) valuable information. Very useful as feedback for teachers in improving the learning activities that have been carried out. Likewise, if male and female students get high results because they answer all the test questions correctly, then the test questions need to be reviewed so that the test questions match the equation of difficulty percentage and ability percentage, from a height. Because the attributes of a proper evaluation are evaluations that consist of components such as validity, reliability, objectivity, practicality, difficulty level, and test item rating elevation. Therefore, it is necessary for every teacher to carry out a good evaluation process in teaching so that each achieves educational goals and improves educational problems, and the benefits of evaluation in teaching Arabic are available to all elements of the education system. The results obtained from this study are as follows: The researcher found that the form of the midterm exam questions for the Arabic language subject at Imam Muslim Islamic Boarding School was in the form of an essay test and there were ten questions in total. The researcher found a classification of difficulty level for each question, 7 moderate questions, and 3 easy questions, so it can be concluded that all questions are good and feasible to use. The researcher found the classification of the level of differential power that was ideal for each question, one question was not good, one question was limited to adequacy, 4 questions were good, and 4 questions were very good. It can be concluded that all questions are considered good and acceptable so that we can use these questions.